Correlation Between Tic Disorders and Serum 25-Hydroxyvitamin D Levels in Chinese Children - Wang, Simei; Xu, Quanmei; Wang, Anqi; Yuan, Fang; Luo, Xiaona; Wang, Yilin; Guo, Miao; Zhang, Yuanfeng; Zhang, Wenjing; Ji, Xiaobing; Ren, Yun; Chen, Yucai (Frontiers in Pediatrics, 2022)
Objective: To explore the correlation between serum 25-hydroxyvitamin D levels and tic disorders (TD) in Chinese children. Methods: We selected 2,960 children with TD and 2,665 healthy controls, aged 5–14 years, from the Department of Neurology of the Shanghai Children's Hospital. Serum 25-hydroxyvitamin D levels and the degree of vitamin D deficiency were compared between patients with TD and heallthy children. Results: Mean serum 25-hydroxyvitamin D level in the TD group was significantly lower than that in the control group (P<0.001). The proportion of patients with 25-hydroxyvitamin D deficiency in the TD group was significantly higher than that in the control group. However, there was no correlation between 25-hydroxyvitamin D deficiency and the severity of TD. In addition, for age-wise comparison, mean levels of 25-hydroxyvitamin D and its deficiency in the TD group were the most significant in children over 9 years of age Conclusion: There is a correlation between 25-hydroxyvitamin D deficiency and TD in Chinese children but not between 25-hydroxyvitamin D deficiency and the severity of TD. There was a correlation of age with deficiency of 25-hydroxyvitamin D; this deficiency was most pronounced among adolescents over the age of 9 years.